2008
DOI: 10.1037/a0014044
|View full text |Cite
|
Sign up to set email alerts
|

Treating co-occurring Axis I disorders in recurrently suicidal women with borderline personality disorder: A 2-year randomized trial of dialectical behavior therapy versus community treatment by experts.

Abstract: This study evaluated whether dialectical behavior therapy (DBT) was more efficacious than treatment by nonbehavioral psychotherapy experts in reducing co-occurring Axis I disorders among suicidal individuals with borderline personality disorder (BPD). Women with BPD and recent and repeated suicidal and/or self-injurious behavior (n = 101) were randomly assigned to 1 year of DBT or community treatment by experts (CTBE), plus 1 year of follow-up assessment. For substance dependence disorders (SDD), DBT patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(72 citation statements)
references
References 29 publications
7
62
0
3
Order By: Relevance
“…These studies have suggested comorbid rates of PTSD among individuals with BPD ranging from 25% to 58% (Zanarini et al 1998; Zlotnick et al 2002; Zlotnick et al 2003; Zimmerman & Mattia, 1999; Zanarini et al 2004; Golier et al 2003; Rusch et al 2007; Famularo et al 1991; Van Den Bosch et al 2003; Yen et al 2002; Harned et al 2008; Linehan et al 2006). Studies have reported similar rates of comorbid BPD among individuals with PTSD to range even more widely between 10% and 76% (Southwick et al 1993; Heffernan & Cloitre, 2000; Shea et al 1999; Zlotnick et al 2002; Feeny et al 2002; Clarke et al 2008; Connor et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have suggested comorbid rates of PTSD among individuals with BPD ranging from 25% to 58% (Zanarini et al 1998; Zlotnick et al 2002; Zlotnick et al 2003; Zimmerman & Mattia, 1999; Zanarini et al 2004; Golier et al 2003; Rusch et al 2007; Famularo et al 1991; Van Den Bosch et al 2003; Yen et al 2002; Harned et al 2008; Linehan et al 2006). Studies have reported similar rates of comorbid BPD among individuals with PTSD to range even more widely between 10% and 76% (Southwick et al 1993; Heffernan & Cloitre, 2000; Shea et al 1999; Zlotnick et al 2002; Feeny et al 2002; Clarke et al 2008; Connor et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…DBT has been examined in more than a dozen randomised controlled trials (RCTs), and has been found to be superior to control conditions in reducing the primary problems it is designed to treat such as suicidal and NSSI behaviours psychiatric hospitalisations, and emergency room visits [9]. However, standard DBT does not specifically target trauma-related features or symptoms, and has only limited effects on PTSD in patients with BPD [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Participants in the DBT condition had half as many suicide attempts, were twice as likely to stay in treatment, had reduced emergency department and inpatient psychiatric care use, and demonstrated less lethal or medically risky suicide attempts (Linehan et al, 2006). Both treatment groups demonstrated significant reductions in NSSI and ratings of depression, and no between-groups differences were detected in anxiety or eating disorders (Hamed et al, 2008). A comparison of DBT to a structured, psychodynamic treatment, transference-focused psychotherapy (TFP) found that individuals in both groups improved on suicidal behaviors but that TFP was associated with improvement across more domains (Clarkin et al, 2007).…”
Section: Randomized Controlled Trials Of Dbt For Bpdmentioning
confidence: 93%